Ratchet mechanism selectively causing idiopathic macrodislodgement of an active-fixation coronary sinus lead: a case report. Issue 6 (28th December 2020) - Golzio, Pier Giorgio; Bissolino, Arianna; Ceci, Raffaele; Frea, Simone
Abstract: Background : 'Idiopathic' lead macrodislodgement may be due to Twiddler's syndrome depending on active twisting of pulse generator within subcutaneous pocket. All leads are involved, at any time from implantation, and frequently damaged. In the past few years, a reel syndrome was also observed: retraction of pacemaker leads into pocket without patient manipulation, owing to lead circling the generator. In other cases, a 'ratchet' mechanism has been postulated. Reel and ratchet mechanisms require loose anchoring, occur generally briefly after implantation, with non-damaged leads. We report the first case of an active-fixation coronary sinus lead selective macrodislodgement involving such ratchet mechanism. Case summary : A 65-year-old man underwent biventricular defibrillator device implantation, with active-fixation coronary sinus lead. Eight months later, he complained of muscle contractions over device pocket. At fluoroscopy, coronary sinus lead was found near to pocket, outside of thoracic inlet. Atrial and ventricular leads were in normal position. After opening pocket, a short tract of coronary sinus lead appeared anteriorly dislocated to generator, while greater length of lead body twisted a reel behind. The distal part of lead was found outside venous entry at careful dissection. Atrial and ventricular leads were firmly anchored. Discussion : Our case is a selective 'Idiopathic' lead macrodislodgement, possibly due to a ratchet mechanism between the lead and the suture sleeve, induced by normal arm motion; such mechanism incredibly, and for first time in literature involves a coronary sinus active-fixation lead. Conclusion : Careful attention should always be paid to secure anchoring even of active-fixation coronary sinus leads.